Rare Presentation of Immunoglobulin G4–Related Disease: Hepatic Mass Lesions Mimicking Metastasis - Yıldırım, Tuba Yılmaz; Çiftçi, Uğur; Huseynov, Javid; Demirtaş, Coşkun Özer; Özdoğan, Osman Cavit (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Yıldırım TY, Çiftçi U, Huseynov J, Demirtaş CÖ, Özdoğan OC. Rare presentation of Immunoglobulin G4–related disease: hepatic mass lesions mimicking metastasis. Turk J Gastroenterol. Published online September 18, 2025. doi:10.5152/ tjg.2025.25211.